Faktor Gelagat (Behavioral Factor) dalam Mempengaruhi Pemutusan Pembelian Rumah - Zainudin, Siti Sarah; Eni, Sabariah (Research in Management of Technology and Business, 2020)
Previous housing reseach discusses on dominan factors influencing individual decisions about owning and rensting housing, but very few have considered behavioural factors in decision making. This paper fills the gap in the literature on dominan factors and if behavioural factors is considered by individual intention to buy or rent in the future. Quantitaive analysis adopted via survey to 87 respondents attached with UTHM Pagoh campus.The analysis finds that there are strong indicators of expectation on economy element through income and wages, whilst socio-demography assumed family composition and constraint on location is the most important. Individual’s perception about constraints on their ability to purchase or rent or predictive of future intentions are not clearly significant to explain behavioural factors in buying or renting decision.